Genetic Variation in Host-Specific Competitiveness of the Symbiont Rhizobium leguminosarum Symbiovar viciae - Boivin, Stéphane; Mahé, Frederic; Debellé, Frédéric; Pervent, Marjorie; Tancelin, Mathilde; Tauzin, Marc; Wielbo, Jerzy; Mazurier, Sylvie; Young, Peter; Lepetit, Marc (Frontiers in Plant Science, 2021)
Legumes of the Fabeae tribe form nitrogen-fixing root nodules resulting from symbiotic interaction with the soil bacteria Rhizobium leguminosarum symbiovar viciae (Rlv). These bacteria are all potential symbionts of the Fabeae hosts but display variable partner choice when co-inoculated in mixture. Because partner choice and symbiotic nitrogen fixation mostly behave as genetically independent traits, the efficiency of symbiosis is often suboptimal when Fabeae legumes are exposed to natural Rlv populations present in soil. A core collection of 32 Rlv bacteria was constituted based on the genomic comparison of a collection of 121 genome sequences, representative of known worldwide diversity of Rlv. A variable part of the nodD gene sequence was used as a DNA barcode to discriminate and quantify each of the 32 bacteria in mixture. This core collection was co-inoculated on a panel of 9 genetically diverse Pisum sativum, Vicia faba and Lens culinaris genotypes. We estimated the relative Early Partner Choice (EPC) of the bacteria with the Fabeae hosts by DNA metabarcoding on the nodulated root systems. Comparative genomic analyses within the bacterial core collection identified molecular markers associated with host-dependent symbiotic partner choice. The results revealed emergent properties of rhizobial populations. They pave the way to identify genes related to important symbiotic traits operating at this level.